Fractional Exhaled Nitric Oxide (FeNo) in Different Asthma Phenotypes. Issue 3 (September 2014) - Gemicioglu, Bilun; Musellim, Benan; Dogan, Ismail; Guven, Kasim
Fractioned exhaled nitric oxide (FeNO) is a noninvasive marker of inflammation in asthmatic patients. FeNO can be used to monitor airway inflammation, but individual responses make tailored interventions based on FeNO difficult. The correlation between the asthma control test (ACT), FEV1, and FeNO was evaluated in this study to ascertain the correct usage of FeNO with different asthma phenotypes regarding their control, allergy, comorbidity, obesity, age, smoking status, and severity. ACT, pulmonary function, and FeNO in 416 asthmatic patients on combined therapy were retrospective evaluated. Correlations between these parameters and the FeNO levels in different asthma phenotypes were calculated. In the study population, FeNO was 31.8 ± 28.5 parts per billion (ppb), FEV1 was 83.4 ± 19% and ACT was 19 ± 5.2. ACT scores were negatively correlated with FeNO (r = −0.31; p = 0.002). FeNO was different in patients with positive and negative skin-prick test (p < 0.05), with and without allergic rhinitis (p < 0.01), and with and without allergic conjunctivitis (p < 0.01). Significantly higher FeNO levels were found with logistic regression analysis only in patients with a history of emergency room visits (ERVs) (p = 0.024). The rate of the ERV of the patients with an ACT score more than or equal to 20 and with a FeNO value of more than 35 ppb was 22.9%, but with a FeNO value of less than 35 ppb was 6.5% (p = 0.004). Allergy and allergic comorbidities may lead to an increase in FeNO levels. Patients with a history of ERV have markedly higher FeNO levels, although they have an ACT score more than or equal to 20.